Considerations of the Warsaw Uprising in “Tygodnik Powszechny” in the Years 1945–1953 - Gryglewski, Krzysztof; Kuliś, Jakub; Pisarski, Jakub; Wiśniewski, Cyprian; Agnieszka Gralak (Vade Nobiscum, tom XXIII/2021: Studia nad XIX i XX wiekiem, 2021)
The purpose of this article was to present in detail the considerations of “Tygodnik Powszechny” journalists on the Warsaw Uprising. In the realities of post-war Poland, the Catholic view presented by “Tygodnik” was clearly different from the materialistic world view promoted by the authorities at the time. Although the editors of this Christian magazine generally avoided topics related to the fate of ordinary civilians in the Polish capital during these dramatic events, they did not hesitate to raise painful topics. The question of the religiosity of the fighters and the figure of Krzysztof Kamil Baczyński were discussed extensively. Although when describing some themes, e.g. the alleged participation of the Russian Liberation Army in the fights, communist myths were reproduced in the narrative of the uprising, the editors of the weekly discussed vividly among themselves, showing different worldviews in the magazine (e.g. the polemic between Wojciech Kętrzyński and Stefan Kisielewski). In connection with the above, it should be stated that “Tygodnik Powszechny”, despite external pressure, approached the subject of the Warsaw Uprising as fully as possible.